Pengaruh budaya akhlak dan iklim kerja terhadap kinerja karyawan mail processing center (MPC) Bandung - Waskito, Saptono Kusdanu; Rahayu, Muji (JPPI (Jurnal Penelitian Pendidikan Indonesia), 2024)
This research explores the impact of ethical culture and work climate on the performance of employees at the Mail Processing Center (MPC) in Bandung. The study aims to analyze the correlation between ethical values embraced within the organizational culture and the overall work atmosphere with the individual and collective performance of MPC employees. The research methodology involves data collection through surveys, interviews, and performance evaluations. The findings of the study reveal significant insights into how ethical culture and work climate contribute to shaping the employee performance landscape at MPC Bandung. The research outcomes provide valuable recommendations for cultivating a positive ethical environment and improving the work climate, ultimately enhancing the overall performance of employees within the Mail Processing Center.